Innovation development to new business in incumbent firms : a case study on the pharmaceutical companies in Finland - Hemminki, Markus (2016)
This thesis examines new business development in incumbent firms in market environment that is changing faster than ever before. The framework of this study, model to the new business development, is created at the literature re-view part of this study and it is tested for incumbent pharmaceutical companies in Finland. Model enables to study differences between traditional and new businesses in incumbent firms, innovation process for new business develop-ment and business ecosystem structure of incumbent firm. The goal of the re-search is to identify ways of incumbent firms to develop new business to be able to compete against more agile companies. Technological development has enabled new players to enter to market. The results reveal that to be able to re-spond to the needs of fast changing markets would incumbent firms benefit if they separate innovation development of new business from traditional busi-ness, structured innovation process in their new business development and of resources from outside the organisation. In addition this study suggests that firms are trying to benefit from co-operation with the parties outside the organ-isation in short or long term. Further study should be conducted in order to be reliable of the results of this study in case of single company or to have overall view from the industry in Finland and to test the model to new business devel-opment in other countries in this industry and in other industries.